Phenotypic and PCR-based identification of bacterial strains isolated from patients with suspected Streptococcus suis infection in Northern Thailand - Tien L.H.T. (2014)
Twenty bacterial strains isolated from the blood of patients with suspected Streptococcus suis infection based on clinical symptoms in northern Thailand between 2009 and 2010 were subjected to phenotypic and genotypic identification. Commercial identification kits and a PCR-based assay targeting the S. suis-specific 16S rDNA sequence correctly identified S. suis isolated from patients in northern Thailand; however, there was a risk of misidentifying S. gallolyticus as S. suis using a PCR assay targeting the S. suis-specific house keeping gene encoding glutamate dehydrogenase. This is the first paper to report S. gallolyticus infection in humans in Thailand.